(3cdGe aj GdLeGY heG jJYdb Hgs - (3YjSi Hf eGSIs
(3ChdgG (B:s
(3efaYI GdLeGY JNaja GdHOf hJSgjd GdENdGW hJScjf GdWHjYI hGdfSd s
(3BNQgG (B:s
(3cdGe ai GdLeGY edMb HGdfSNI GdJi fbdJ YfgG gPg GdfSNI hHZjQ NWgG JeJ ebGdI YjSi Hf eGSI ai GdLeGY heG jJYdb Hg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/12) s
Keywords: (3GdadSaI hGdefWbs